Valoración económica del servicio ecosistémico de almacenamiento de carbono en cuatro suelos espodosoles de la ciudad universitaria Zungarococha, 2022 - Chavez Sarmiento, Guillermo Paul (2024)
The main purpose of this research is to economically evaluate the carbon storage ecosystem service provided by the spodosol taxonomic classification soils in the university city of Zungarococha. This work is framed as a descriptive and observational quantitative research design, with a cross-sectional measurement. Four points were selected in the white sand forest of the National University of the Peruvian Amazon to make pits and carry out laboratory processes. The objective is to generate an estimate of the carbon not released in the soils and calculate the number of tons stored. In the first pit, a carbon deposit equivalent to 356.27 t/ha was found, economically valued at 28,811.23 euros. Pit 2 showed a carbon storage of 560.3 t/ha, with a value of 45,311.05 euros. Pit 3 stored 2,193.38 t/ha, valued at 177,385.73 euros. Finally, pit 4 recorded 1,522.7 t/ha and 123,140.82 euros in its economic value. In conclusion, spodosol soils tend to accumulate carbon in the spodic horizon, presenting a high economic value, thus showing the importance of these soils for their conservation.